Community participation in solid waste management in urban settlements: A case of Mbeya City Council, Tanzania - Said, Yahaya H. (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirement for award of the degree of Masters of Research and Public Policy (MRPP) of the Mzumbe University